Polar bear skin rug - Photograph ... - Campbell, Sandy (University of Alberta Library, 2011)
This polar bear was taken many years ago in the Yukon. The skin is mounted on two layers of red heavy cotton fabric. The skin was acquired by a private collector, located in western Alberta, in about 2000. ...